Physiological implications of life at the forest interface of oil palm agriculture: blood profiles of wild Malay civets (Viverra tangalunga). Issue 1 (30th December 2020) - Evans, Meaghan N; Guerrero-Sanchez, Sergio; Kille, Peter; Müller, Carsten T; Bakar, Mohd Soffian Abu; Goossens, Benoit
Abstract : Agriculture is a major threat to tropical biodiversity. We determined the first hematology and serum biochemistry panels for wild Malay civets persisting within a fragmented landscape. In addition to expected biological drivers of variation, select blood parameters predictably varied with proximity to oil palm agriculture. Abstract: Agricultural development is a major threat to global biodiversity, and effective conservation actions are crucial. Physiological repercussions of life alongside human-modified landscapes can undermine adaptable species' health and population viability; however, baseline data are lacking for many wildlife species. We assessed the physiological status of a generalist carnivore, the Malay civet ( Viverra tangalunga ), persisting within an extensively human-modified system in Sabah, Malaysian Borneo. We characterized hematology and serum biochemistry panels from civets sampled across a mosaic landscape comprising tropical forest fragments and oil palm plantations. Intra-population variation in certain blood parameters were explained by expected biological drivers such as sex, age category and sampling season. Furthermore, we determined several erythrocyte measures, immune cell counts and dietary biochemistry markers significantly varied with proximity to oil palm plantation boundaries. These findings were supported by a case study, whereby blood profiles of GPS collared male civets were contrasted based on their exclusive use of forests or use of oil palm plantations. These data provide robust and valuable first insights into this species' physiological status and suggest agricultural landscapes are impacting the persisting population.